The Influence of Teacher Readiness and Motivation on Student Learning Achievement at SMPN 5 Rangsang - Siti Aisah; Nurmalina; Ramdhan Witarsa (ASIAN: Indonesian Journal of Learning Development and Innovation, 2024)
This study aims to determine the influence of teacher readiness and motivation on student achievement at SMPN 5 Rangsang. The study uses a quantitative approach with a survey method. The population in this study consists of all eighth-grade students at SMPN 5 Rangsang, with a sample of 19 students selected through a saturated sampling technique. Data were collected using questionnaires on teacher readiness and motivation. The data analysis technique used is multiple linear regression. The results show that teacher readiness has a significant effect on student achievement. Additionally, teacher motivation also has a significant impact on student achievement. Together, teacher readiness and motivation significantly contribute to improving student achievement. Therefore, efforts to enhance teacher readiness and motivation are necessary to improve student achievement at SMPN 5 Rangsang.